Stress–response relationships related to ageing and death of orthodox seeds: a study comparing viability and RNA integrity in soya bean (Glycine max) cv. Williams 82. Issue 2 (15th June 2020) - Walters, Christina; Fleming, Margaret B.; Hill, Lisa M.; Dorr, Emma J.; Richards, Christopher M.
Abstract: Characterizing non-lethal damage within dry seeds may allow us to detect early signs of ageing and accurately predict longevity. We compared RNA degradation and viability loss in seeds exposed to stressful conditions to quantify relationships between degradation rates and stress intensity or duration. We subjected recently harvested ('fresh') 'Williams 82' soya bean seeds to moisture, temperature and oxidative stresses, and measured time to 50% viability (P50) and rate of RNA degradation, the former using standard germination assays and the latter using RNA Integrity Number (RIN). RIN values from fresh seeds were also compared with those from accessions of the same cultivar harvested in the 1980s and 1990s and stored in the refrigerator (5°C), freezer (−18°C) or in vapour above liquid nitrogen (−176°C). Rates of viability loss (P50 −1 ) and RNA degradation (RIN⋅d −1 ) were highly correlated in soya bean seeds that were exposed to a broad range of temperatures [holding relative humidity (RH) constant at about 30%]. However, the correlation weakened when fresh seeds were maintained at high RH (holding temperature constant at 35°C) or exposed to oxidizing agents. Both P50 −1 and RIN⋅d −1 parameters exhibited breaks in Arrhenius behaviour near 50°C, suggesting that constrained molecular mobility regulates degradation kinetics of dry systems. We conclude that the kinetics of ageing reactions at RH near 30% can be simulated by temperatures up to 50°C and that RNA degradation can indicate ageing prior to and independent of seed death.